Antibody profiles to wheat germ cell-free system synthesized Plasmodium falciparum proteins correlate with protection from symptomatic malaria in Uganda. Issue 6 (7th February 2017) - Kanoi, Bernard N.; Takashima, Eizo; Morita, Masayuki; White, Michael T.; Palacpac, Nirianne M.Q.; Ntege, Edward H.; Balikagala, Betty; Yeka, Adoke; Egwang, Thomas G.; Horii, Toshihiro; Tsuboi, Takafumi
Highlights: WGCFS generated P. falciparum recombinant proteins are highly immunoreactive to human sera. P. falciparum -exposed individuals raise antibodies to hundreds of parasite proteins. Fifty-three known and novel antigens are plausible targets of protective immunity. Secreted apical merozoite and sporozoite antigens are potential malaria vaccine candidates. WGCFS and AlphaScreen system are invaluable tools for malaria vaccine candidate discovery. Abstract: The key targets of protective antibodies against Plasmodium falciparum remain largely unknown. In this study, we determined immunoreactivity to 1827 recombinant proteins derived from 1565 genes representing ∼30% of the entire P. falciparum genome, for identification of novel malaria vaccine candidates. The recombinant proteins were expressed by wheat germ cell-free system, a platform that can synthesize quality plasmodial proteins that elicit biologically active antibodies in animals. Sera were obtained from indigenous residents of a malaria endemic region in Northern Uganda who were enrolled at the start of a rainy season and prospectively monitored for symptomatic malaria episodes for a year. Immunoreactivity to sera was determined by AlphaScreen; a homogeneous high-throughput system that detects protein interactions. Our analysis revealed antibody responses to 128 proteins that significantly associated with protection from symptomatic malaria. From 128 proteins, 53 were down-selected as the most plausible targets of host protective immune response by virtue of having a predicted signal peptide and/or transmembrane domain(s), or confirmed localization on the parasite surface. The 53 proteins comprised of not only previously characterized vaccine candidates but also uncharacterized proteins. Proteins involved in erythrocyte invasion; RON4, RON2 and CLAG3.1 and pre-erythrocytic proteins; SIAP-2, TRAP and CelTOS, were recommended for prioritization for further evaluation as vaccine candidates. The findings clearly demonstrate that generation of the protein library using the wheat germ cell-free system coupled with high throughput immunoscreening with AlphaScreen offers new options for rational discovery and selection of potential malaria vaccine candidates.